Efektivitas Penggunaan Media Video Meteri Gunung Api Terhadap Hasil Belajar Siswa Kelas VII Di SMP Negeri 2 Gatak, Sukoharjo - Nugroho, Ridwan Arif; , Drs. Suharjo, M.Si (2016)
SMP Negeri 2 Gatak, Sukoharjo are addressed in Hamlet Trangsang, District Gatak, Sukoharjo regency of Central Java province. The learning method using video media in conveying the material volcanic influence on learning outcomes. This study using videos as a method of presenting the material. Material volcano that requires in-depth explanation of how the appearance and shape of guuung fire itself generated through video learning. So that learners can easily find out how exactly and what the volcano. This study using videos to test the effectiveness of the learning effect on student learning outcomes. This study uses five classes as a population that is class A to class VII VII E which in turn uses two classes as a sample of the research that kkelas VII D as experimental class and class VII E as the control class. Grading taken for the study is the result of the pre test of the entire class population. Further research determined that two classes of experimental class and control class. Class experiment in learning using video media while the control group using conventional methods. Data retrieval is assessed is the level of students' knowledge with the calculation of pre-test and post test. Data were analyzed using normality test, homogeneity test, and test the hypothesis that semunaya using SPSS 21. The data obtained show that control class scored an average of 61.2 while the experimental group scored an average of 91.03. Pre test in this study received sig (2-tailed) is greater than the probability value 0.128> H0 then the class gets the value Sig post test (two-tailed lower than the value probalititas 0.00 <0.05 H0 test with type of simple paired test showed sig (2-taled) lower than the 0.00 probability value> 0.05 then H0 is rejected. the conclusion that there was an increase learning outcomes using video media volcanic material in SMP Negeri 2 Gatak, Sukoharjo.